Capacidad antioxidante de pepita de Citrullus lanatus (sandía regional), y su uso en fortificar panes - Sifuentes Sánchez, Deysi Jiomira (2023)
Watermelon is one of the most consumed fruits in the Loreto region, as a consequence its consumption generates a large amount of seeds that are discarded. The objective of this work was to study the antioxidant activity and the total phenol content of regional watermelon seed extracts, likewise, added value was given to these seeds to obtain highly nutritious fortified breads. We used two methods to determine antioxidant activity: DPPH and ABTS. The results found indicate that watermelon seeds have considerable antioxidant activity, since we found inhibition values of DPPH between 27.21 to 71.15% and of ABTS between 12.41 to 20.23%. Regarding the production of breads, these were fortified with different percentages of watermelon seed flakes. It was found that the incorporation of the sand flakes, necessary the humidity of the panels, and on the contrary, increased the fat and ash content. Likewise, according to the sensory test carried out, no significant differences were found between the treatments, although it was formulation 1 that had the highest score. Therefore, it can be concluded that the use of watermelon seeds can be an ideal alternative to enrich food products with antioxidant compounds.